Generation of High Energy Gamma-ray by Laser Compton Scattering of 1.94-μm Fiber Laser in UVSOR-III Electron Storage Ring. (June 2016) - Zen, Heishun; Taira, Yoshitaka; Konomi, Taro; Hayakawa, Takehito; Shizuma, Toshiyuki; Yamazaki, Junichiro; Kii, Toshiteru; Toyokawa, Hiroyuki; Katoh, Masahiro; Ohgaki, Hideaki
Abstract: Development of a laser Compton scattering (LCS) gamma-ray source in the UVSOR-III storage ring has been proposed to perform basic research on non-destructive three dimensional isotope imaging. As the first step of the development, a numerical simulation was performed to evaluate the performance of the gamma-ray source. The expected total flux is about 1×10 7 photons/s when a 1.94-μm CW fiber laser with the maximum power of 5 W collides with 300-mA electron beam circulating in the storage ring. The maximum gamma-ray energy and the total flux available were measured in experiment and determined as 5403 ± 16 keV with 1×10 7 photons/s, respectively. The electron beam energy was evaluated as 746 ± 1 MeV from the measured maximum gamma-ray energy. From the numerical calculation and the experimental result, the energy spread of 2.9% in full width at half maximum and the flux of 4×10 5 photons/s are expected for the LCS gamma-ray beam when a collimator with 2-mm hole is used to limit the scattered angle. The quality of gamma-ray beam generated in UVSOR-III is enough to perform a basic study on the non-destructive three dimensional isotope imaging.